Estrutura da comunidade arbórea-arbustiva em uma área de vegetação ripária no norte do Paraná, Brasil. - Garcia, Letícia Mônica (2015)
Due to the importance of riparian vegetation, and the need of preservation, this study aims to analyze the structure of arboreal community from riparian vegetation in the left border of Morangueiro Brook, in the farm Cesumar. Floristic similarities were analyzed, and species were organized in successional categories and dispersion syndromes. This study was elaborated in a remnant riparian forest, with an area of 58 ha, in Maringá, Northern Paraná, (23º20 36.29 S e 51º51 40.59 W), and 425m of altitude. For the phytosociological survey was used the method of plots, they were delimitated in two blocks with 56 plots each, with 10x10m, 10m parallels to the bed of the brook for 10 m perpendicular, with a total sample area of 11,200 m². Where were included the trees and the shrubs with PAP ≥ 15 cm. Were sampled 1289 arboreal and shrub individual belonging to 73 species, 61 genera and 30 families. The richest floristic families are: Fabaceae with 17 species, followed by Myrtaceae with 7, Salicaceae with five, Lauraceae, Rutaceae e Sapindaceae with four, all together are 56% of the species. The most important species in IVI are: Sebastiania commersoniana, Campomanesia xanthocarpa, dead category, Bastardiopsis densiflora, Myrocarpus frondosus, Nectandra megapotamica e Trichilia catigua, are 49,06% from the total IVI. The diversity index of Shannon-Weaner (H ) were 3,42, indicating a high biological diversity. The Sørensen (ISs) índex of similarity, calculated with this and other ten phytosociological surveys in Phyto-ecological region from semideciduous forest resulted in values from 17.77 to 48.17%. The successional category, the ecological group of early secundaries got high concentration of individuals, indicating that the community is in process of regeneration, that succession is occurring between the species. The 72 species evaluated for dispersion syndrome, approximately 54% are zoochorous, 23% are autochorous, 3% are autochorous and 10% were not classified. The high percentual of zocóricas species may indicate that in this region occur the establishment of gene flow between the species population.